2015
DOI: 10.1177/1753944715589717
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED: Differential expression of the angiotensin-(1-12)/chymase axis in human atrial tissue

Abstract: Objective Heart chymase rather than angiotensin converting enzyme has higher specificity for angiotensin (Ang) I conversion into Ang II in humans. A new pathway for direct cardiac Ang II generation has been revealed through the demonstration that Ang-(1-12) is cleaved by chymase to generate Ang II directly. We address here whether Ang-(1-12) and chymase gene expression and activity are detected in the atrial appendages of 44 patients (10 females) undergoing heart surgery for the correction of valvular heart di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
21
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 55 publications
2
21
0
Order By: Relevance
“…20,21 Briefly, 50-100 μg of LV native plasma membranes (PMs) were preincubated with or without chymase inhibitor (chymostatin, 50 μM) for 15 min. Other inhibitors (lisinopril, SCH39373, MLN-4760, amastatin, bestatin, benzylsuccinate and p-chlomercuribenzoate, each 50 μM) were also added to inhibit the renin-angiotensin enzymes (ACE/ACE2/neprilysin), peptidases and metalloprotease.…”
Section: Methodsmentioning
confidence: 99%
“…20,21 Briefly, 50-100 μg of LV native plasma membranes (PMs) were preincubated with or without chymase inhibitor (chymostatin, 50 μM) for 15 min. Other inhibitors (lisinopril, SCH39373, MLN-4760, amastatin, bestatin, benzylsuccinate and p-chlomercuribenzoate, each 50 μM) were also added to inhibit the renin-angiotensin enzymes (ACE/ACE2/neprilysin), peptidases and metalloprotease.…”
Section: Methodsmentioning
confidence: 99%
“…The amino acid sequence of this novel RAS peptide [Ang-(1-12)] is similar to the sequence of Ang I plus -Val 11 -Ile 12 (in human) and -Leu 11 -Try 12 (in rodent) position of the C-terminus. Compared to Ang I, higher concentration of Ang-(1-12) has been detected in hypertensive rat and diseased human tissues [88, 89]. …”
Section: Formation Of Ang II By Tissue Specific Chymasementioning
confidence: 99%
“…In addition, recent work showed that ir-Ang-(1-12) expression is significantly higher in human left atria appendage (35.37 ± 6.24 units) compared to the expression of the peptide in the right atrium (19.38 ± 2.38 units, p=0.031). The increased Ang-(1-12) expression was associated with high left atrium chymase activity [76]. A differential content or expression of endocrine peptides in the heart has been reported in several species [77;78].…”
Section: Novel Pathways Upstream From Angiotensin I –The New Research–mentioning
confidence: 99%